2011
DOI: 10.1128/iai.01017-10
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenicity of an EntericCitrobacter rodentiumInfection Is Enhanced by Deficiencies in the Antioxidants Selenium and Vitamin E

Abstract: The pathogenesis of a Citrobacter rodentium infection was evaluated in mice fed diets with a single deficiency in either selenium or vitamin E or with a double deficiency in both selenium and vitamin E compared to mice on nutritionally adequate diets. Mice fed the selenium-and vitamin E-deficient diet for 6 weeks had increased loads of C. rodentium in the colon and spleen, which were not observed in mice fed either of the singly deficient diets or the adequate diet. Infected mice fed the doubly deficient diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 60 publications
6
30
0
Order By: Relevance
“…Increased pathology was accompanied by a large increase in infiltrating cells that correlated with increased expression of several members of the CXCL chemokine family as well as CCL2. These results are very similar to those obtained with mice fed a selenium-and vitamin E double-deficient diet for 6 weeks [27]. It is known that vitamin E deficiency exacerbates selenium deficiency [41], and this may account for the similar results obtained in a shorter timeframe in mice fed a diet deficient in both selenium and vitamin E.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased pathology was accompanied by a large increase in infiltrating cells that correlated with increased expression of several members of the CXCL chemokine family as well as CCL2. These results are very similar to those obtained with mice fed a selenium-and vitamin E double-deficient diet for 6 weeks [27]. It is known that vitamin E deficiency exacerbates selenium deficiency [41], and this may account for the similar results obtained in a shorter timeframe in mice fed a diet deficient in both selenium and vitamin E.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous work established that deficiencies in selenium altered the clearance of a gastrointestinal nematode parasite, Heligmosomoides polygyrus, from mice [25,26]. Furthermore, a double deficiency in selenium and vitamin E resulted in increased pathology in response to infection of mice with C. rodenitum [27]. Here, we provide evidence that selenium is critical for optimal resistance and reduced pathogenicity to infection with C. rodentium.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Interestingly, this increased neutrophil influx was also associated with upregulated expression of the genes for the innate immune response-related cytokines IL-1␤, iNOS, IL-17a, IL-6, and TNF-␣ at day 14 p.i. In agreement with previous reports, we found that the expression of the genes for these innate immune cytokines was higher in infected, vehicle-treated mice than in noninfected controls at peak infection (22,48). These cytokines play a significant role in host defense and clearance of C. rodentium early during infection (13,20,25,53).…”
Section: Discussionsupporting
confidence: 81%
“…Sedeficiency has been shown to exacerbate infection of mice with Citrobacter rodentium, which shares many characteristics with human enteropathogenic (EPEC13) and enterohemorrhagic E. coli (EHEC) (233). Infections with this pathogen in mice produce robust immune responses characterized by a mixed Th1/Th17 response (100,114).…”
Section: Intestinal Inflammation and Food-borne Illnessesmentioning
confidence: 99%